Unlocking digital potential: Exploring the drivers of employee dynamic capability on employee digital performance in Chinese SMEs-moderation effect of competitive climate - Wang, Guifang; Niu, Yue; Dato Mansor, Zuraina; Leong, Yee Choy; Yan, Zhen (Elsevier, 2024)
While dynamic capabilities have been described as crucial for achieving organizational performance in dynamic environments, there has been limited scholarly distinction between dynamic capabilities and employee dynamic capabilities (EDC), especially in the digital era. Consequently, a knowledge gap has emerged. To address this void, this paper aims to investigate the driving factors of EDC and their impact on employee digital performance (EDP). Simultaneously, incorporating the competitive climate (CC) as a moderating variable between employee dynamic capabilities and employee digital performance addresses theoretical gaps in specific regions in China, particularly in small and medium-sized enterprises (SMEs). This study utilizes survey data from SMEs in four Chinese provinces: Shanghai, Guizhou, Guangdong, and Anhui. It employs CB-SEM (AMOS) to analyze the new conceptual framework. Firstly, the research uncovers that the positive relationship between digital capabilities and employee digital performance necessitates employee dynamic capabilities as a mediator. Secondly, there exists a direct and indirect relationship between organizational learning and employee digital performance. Finally, this study discerns that the competitive climate moderates the relationship between employee dynamic capabilities and employee digital performance. This finding demonstrates remarkable alignment with the competitive culture in specific regions of China. The research results encourage SMEs to seize the opportunities presented by emerging digital technologies and industry digitization trends. They should commit to embracing new digital technologies, enhancing digital capability, strengthening organizational learning, fostering a positive competitive climate, and focusing on the development of employee dynamic capability to enhance their competitive edge. The findings of this research contribute not only to academic inquiry but also furnish pertinent decision-making references for relevant departments. © 2024 The Authors